A framework and case study to systematically identify long‐term insect abundance and diversity datasets - Eliza M. Grames; Graham A. Montgomery; Douglas H. Boyes; Lynn V. Dicks; Matthew L. Forister; Tanner A. Matson; Shinichi Nakagawa; Kit S. Prendergast; Nigel G. Taylor; Morgan W. Tingley; David L. Wagner; Thomas E. White; et al. (Conservation Science and Practice, 2022)
Abstract Biodiversity is in crisis, and insects are no exception. To understand insect population and community trends globally, it is necessary to identify and synthesize diverse datasets representing different taxa, regions, and habitats. The relevant literature is, however, vast and challenging to aggregate. The Entomological Global Evidence Map (EntoGEM) project is a systematic effort to search for and catalogue studies with long‐term data that can be used to understand changes in insect abundance and diversity. Here, we present the overall EntoGEM framework and results of the first completed subproject of the systematic map, which compiled sources of information about changes in dragonfly and damselfly (Odonata) occurrence, abundance, biomass, distribution, and diversity. We identified 45 multi‐year odonate datasets, including 10 studies with data that span more than 10 years. If data from each study could be gathered or extracted, these studies could contribute to analyses of long‐term population trends of this important group of indicator insects. The methods developed to support the EntoGEM project, and its framework for synthesizing a vast literature, have the potential to be applied not only to other broad topics in ecology and conservation, but also to other areas of research where data are widely distributed.